Distribution of six taxa in the family Bosminidae Baird (Crustacea: Branchiopoda: Anomopoda) in the plankton of lakes and reservoirs within the continental United States, including expanded range of the invasive cladoceran Bosmina (Eubosmina) coregoni Baird - Beaver, John R.; Renicker, Thomas R.; Tausz, Claudia E.; Vitanye, Benjamin T. (Zootaxa, 2018)
Updated range distributions in lakes and reservoirs of the continental United States are provided for six taxa in the family Bosminidae (Bosmina (Bosmina) cf. longirostris (Müller), Bosmina (Eubosmina) coregoni Baird, Bosmina cf. longispina Leydig, Bosmina (Liederobosmina) cf. tubicen Brehm, Bosmina (Liederobosmina) cf. hagmanni Stingelin, and Bosminopsis deitersi Richard), an ecologically important and taxonomically confusing group. This paper provides updated range distribution and information on the westward expansion of the invasive species Bosmina (Eubosmina) coregoni, which was first established in the Great Lakes in the late 1960’s. Current survey data are compared with previous distribution records and discussed in the context of environmental variables.